2018
DOI: 10.1002/mgg3.415
|View full text |Cite
|
Sign up to set email alerts
|

Genetics in mainstream medicine: Finally within grasp to influence healthcare globally

Abstract: A modern genomics ecosystem has emerged. This commentary describes recent trends in clinical genomics that enable its successful integration in mainstream medicine. The rapid expansion of clinical genomics will have a positive impact on the healthcare of individuals worldwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Second, this review found that while many tools had more than one intended clinical setting, half of these studies took place in the oncology setting. Genetic testing is becoming mainstream outside of oncology across various specialties, including neurology, cardiology and nephrology, where there is often a lack of genetic counselling support 46 47. Patients and their caregivers in these specialties and those being tested outside of the traditional clinical genetics settings may have distinct needs from patients in oncology but their needs have been inadequately addressed by existing digital tools.…”
Section: Discussionmentioning
confidence: 99%
“…Second, this review found that while many tools had more than one intended clinical setting, half of these studies took place in the oncology setting. Genetic testing is becoming mainstream outside of oncology across various specialties, including neurology, cardiology and nephrology, where there is often a lack of genetic counselling support 46 47. Patients and their caregivers in these specialties and those being tested outside of the traditional clinical genetics settings may have distinct needs from patients in oncology but their needs have been inadequately addressed by existing digital tools.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a clinical geneticist said “It is important medical information, as it would be for other medical investigations, so why wouldn’t you share it?” (P20). The progressively more mainstream role of genetics in healthcare also underpinned this view (Aradhya and Nussbaum, 2018). This was often echoed by consumers who recognised the benefits of having results accessible to all their treating clinicians.…”
Section: Resultsmentioning
confidence: 99%
“…(P20). The progressively more mainstream role of genetics in healthcare also underpinned this view (Aradhya and Nussbaum, 2018). This was often echoed by consumers who recognised the benefits of having results accessible to all their treating clinicians.…”
Section: Themesmentioning
confidence: 99%
“…Continuous advances in DNA sequencing over the last two decades have enabled cutting edge life sciences research by providing access to increasing amounts of genomic, transcriptomic, and epigenetic data across all fields of biology. Methods for massively parallel sequencing of clonally-amplified short DNA fragments, also known as second-generation sequencing, have reduced the sequencing cost of a whole human genome by over 6 orders of magnitude, from $3B estimated for the Human Genome Project 1 to under $1000 per genome 2 enabling a rapidly growing set of clinical applications ranging from carrier screening and prenatal testing to tumor profiling and early cancer detection [3][4][5][6] . However, sequencing cost reduction has stalled in recent years around the $6-10/Gb price point 2 .…”
Section: Introductionmentioning
confidence: 99%